The relationship between measurement error and photometer cosine response performance index. (February 2016) - Young, R; Senft, M; Tribes, D; Peters, F
Performance indicesf ' 1 through to f 12 are used in selecting and comparing photometers. These indices are expressed in percent with the ideal being 0%. Uncertainties may be expressed in the same way and performance indices are often mistaken for uncertainties. There is no functional relationship between performance indices and uncertainties but a limiting relationship has been previously established forf ' 1 . Here, an analogous limiting relationship is shown for the cosine response index, f 2, by simulating a range of realistic photometer responses and measurements of a sample of fourteen lighting scenarios. For most lighting scenarios the limiting error is the f 2 value plus 1%. However, some (mainly outdoor) scenarios give much larger errors so care is required in estimating errors in such lighting measurements.